Immortalized human choroid plexus endothelial cells enable an advanced endothelial-epithelial two-cell type in vitro model of the choroid plexus - Muranyi, Walter; Schwerk, Christian; Herold, Rosanna; Stump-Guthier, Carolin; Lampe, Marko; Fallier-Becker, Petra; Weiß, Christel; Sticht, Carsten; Ishikawa, Hiroshi; Schroten, Horst (iScience, 2022)
The choroid plexus (CP) is a highly vascularized structure containing endothelial and epithelial cells located in the ventricular system of the central nervous system (CNS). The role of the fenestrated CP endothelium is under-researched and requires the generation of an immortalized CP endothelial cell line with preserved features. Transduction of primary human CP endothelial cells (HCPEnC) with the human telomerase reverse transcriptase (hTERT) resulted in immortalized HCPEnC (iHCPEnC), which grew as monolayer with contact inhibition, formed capillary-like tubes in Matrigel, and showed no colony growth in soft agar. iHCPEnC expressed pan-endothelial markers and presented characteristic plasmalemma vesicle-associated protein-containing structures. Cultivation of iHCPEnC and human epithelial CP papilloma (HIBCPP) cells on opposite sides of cell culture filter inserts generated an in vitro model with a consistently enhanced barrier function specifically by iHCPEnC. Overall, iHCPEnC present a tool that will contribute to the understanding of CP organ functions, especially endothelial-epithelial interplay.